Azerbaijan - Bangladesh: Bilateral trade opportunities and potential exporting sector for Azerbaijan - S.M. Rashed Jahangir; Fariz Saleh Ahmadov (Journal of Contemporary Economic and Business Issues, 2019)
Trade is an essential indicator for measuring a country's economic condition. It is also an effective way of balancing goods and services among countries. No country in the modern world is self-sufficient in goods and services. That is the reason for emerging the economic concept of trade. The primary purpose of the study is to analyse the trade opportunities between Azerbaijan and Bangladesh, as well as to demonstrate the potential resurrection of cotton industry as an important export sector in Azerbaijan. The whole analysis relies on secondary data, such as articles, newspapers, and websites-mainly the International Trade Centre (ITC) and the State Statistical Committee of the Republic of Azerbaijan. The study concludes that there is an opportunity for potential bilateral trade relation between Azerbaijan and Bangladesh based on their export and import items. In addition, the cotton industry has an enormous potentiality to become an important export sector in Azerbaijan.
Keywords: B17; F23; L67; 330; Bilateral trade relation; export and import; cotton industry